2020
DOI: 10.1021/acs.jctc.0c00634
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Double-System Single-Box: A Nonequilibrium Alchemical Technique for Absolute Binding Free Energy Calculations: Application to Ligands of the SARS-CoV-2 Main Protease

Abstract: In the context of drug−receptor binding affinity calculations using molecular dynamics techniques, we implemented a combination of Hamiltonian replica exchange (HREM) and a novel nonequilibrium alchemical methodology, called virtual double-system single-box, with increased accuracy, precision, and efficiency with respect to the standard nonequilibrium approaches. The method has been applied for the determination of absolute binding free energies of 16 newly designed noncovalent ligands of the main protease (3C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 79 publications
0
79
0
Order By: Relevance
“…In the present work we have performed a combined simulation based on classical MD and ab initio FMO methods for the analysis of ligand binding in the SARS-CoV-2 M pro -N3 complex system, thus finding the importance of statistical evaluation of interactions by employing a thousand of dynamically fluctuating structures. Recent studies 17,[20][21][22][23]53,[55][56] concerning SARS-CoV-2 proteins have shed light on the importance of "dynamic" aspects, and our quantum-chemical work accords with this direction.…”
Section: Resultsmentioning
confidence: 99%
“…In the present work we have performed a combined simulation based on classical MD and ab initio FMO methods for the analysis of ligand binding in the SARS-CoV-2 M pro -N3 complex system, thus finding the importance of statistical evaluation of interactions by employing a thousand of dynamically fluctuating structures. Recent studies 17,[20][21][22][23]53,[55][56] concerning SARS-CoV-2 proteins have shed light on the importance of "dynamic" aspects, and our quantum-chemical work accords with this direction.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the poor accuracy of AD4 was also revealed when the docking results were compared with NEMD simulations, = 0.36. 64 The MD simulations would be then accomplished. FEP approach was indicated that it provided the most accurate results, FEP = 0.80 ± 0.06, compared with the respective experiments.…”
Section: Resultsmentioning
confidence: 99%
“…It is probably caused by the difference in scoring functions as indicated by prior observations. 36 Furthermore, in the prior work, 64 AD4 gave poor correlation, = 0.36, with the ∆ Jarzynski , which obtained via NEMD simulations, 33 one of the most accurate free energy approaches until then. Therefore, it may argue that Vina is the appropriate protocol for preliminary assessment of the ligand-binding affinity to the SARS-CoV-2 Mpro.…”
Section: Molecular Docking Calculationsmentioning
confidence: 96%
“…It should be noted that the poor accuracy of AD4 was also revealed when the docking results were compared with the NEMD simulations, R = 0.36. 74 …”
Section: Discussionmentioning
confidence: 99%